Considering counter narratives : narrating, resisting, making sense - Bamberg, Michael G. W., 1947-; Andrews, Molly (Studies in narrative, 2004)
Counter-narratives only make sense in relation to something else, that which they are countering. The very name identifies it as a positional category, in tension with another category. But what is dominant and what is resistant are not, of course, static questions, but rather are forever shifting placements. The discussion of counter-narratives is ultimately a consideration of multiple layers of positioning. The fluidity of these relational categories is what lies at the center of the chapters and commentaries collected in this book. The book comprises six target chapters by leading scholars.